OsARF16, a transcription factor regulating auxin redistribution, is required for iron deficiency response in rice (Oryza sativa L.). (February 2015) - Shen, Chenjia; Yue, Runqing; Sun, Tao; Zhang, Lei; Yang, Yanjun; Wang, Huizhong
Highlights: The rice mutant osarf16 was used for this study. OsARF16 is involved in the iron deficiency response. The expression of OsARF16 was induced in the roots and shoots by Fe deprivation. OsARF16-medicated auxin signaling affects iron signaling. Abstract: Plant response to iron deficiency is the most important feature for survival in Fe-limited soils. Several phytohormones, including auxin, are involved in iron uptake and homeostasis. However, the mechanisms behind how auxin participates in the iron deficiency response in rice are largely unknown. We found that OsARF16 was involved in the iron deficiency response and the induction of iron deficiency response genes. Most Fe-deficient symptoms could be partially restored in the osarf16 mutant, including dwarfism, photosynthesis decline, a reduction in iron content and root system architecture (RSA) regulation. OsARF16 expression was induced in the roots and shoots by Fe deprivation. Restoration of the phenotype could also be mimicked by 1-NOA, an auxin influx inhibitor. Furthermore, the qRT-PCR data indicated that the induction of Fe-deficiency response genes by iron deficiency was more compromised in the osarf16 mutant than in Nipponbare . In conclusion, osarf16, an auxin insensitive mutant, was involved in iron deficiency response in rice. Our results reveal a new biological function for OsARF16 and provide important information on how ARF-medicated auxin signaling affects iron signaling and the iron deficiency response. This work may help us to improve production or increased Fe nutrition of rice to iron deficiency by regulating auxin signaling.